Why Infrastructure Financing Facilities Often Fall Short of Their Objectives - Klingebiel, Daniela; Ruster, Jeff (World Bank, Washington, DC, 2015)
To encourage the private funding and provision of infrastructure services, governments have used specialized financing facilities to offer financial support to investors, often in the form of grants, soft loans, or guarantees. The authors present case studies of infrastructure financing facilities in various stages of development in Colombia, India, and Pakistan. They also present case studies of government-sponsored financing facilities (not of infrastructure) in Argentina, and Moldova. They find that these facilities have often fallen short of their objectives for two main reasons. First, the environment was not conducive to private participation in infrastructure because of poor sector policies, an unstable macroeconomic environment, and inadequate financial sector policies, among other reasons. Second, the facility was faulty in design - in terms of sectors targeted, pricing of instruments, and consistency of objectives, and instruments.